Rapid weight loss (RWL) method on game performance of martial art athletes - Imam Hariadi; Nurrul Riyad Fadhli; Taufik Taufik; Dona Sandy Yudasmara; Eldiene Zaura I’tamada; Rida Hanania (Jurnal Keolahragaan, 2022)
Martial athletes use the rapid weight loss (RWL) method as a strategy to lose weight quickly before competing. This study was conducted to examine the prevalence of the magnitude of the impact of the RWL method used as a way to lose weight by running using a sauna suit on the physical, physiological, psychological, and performance conditions of martial athletes. The population in this study were martial arts athletes throughout Indonesia. This study uses a descriptive method by collecting data through a questionnaire instrument on google Forms which is distributed to martial athletes, especially in the fighting class. The results of the identification through the instrument were then analyzed using descriptive statistics. The results n this study were 88 martial arts athletes using the weight loss method by running using a sauna suit. The impact that occurred on athletes all experienced more than one impact of RWL on the athlete's physical condition, physiological, psychological, and performance of martial athletes which included athletes experiencing 19% of martial arts athletes experiencing muscle cramps, 26% of athletes' body temperature increasing, 7% increasing heart rate, 1% athletes experience dyspnea, 3% athletes experience injuries, 8% athletes feel irritable/increased temperament, 49% athletes experience increased fatigue, 16% athletes experience decreased performance, 9% athletes experience stress, and 17% athletes feel their sports interest is reduced.